Pengaruh Pemberian Kayu Apu (Pistia stratiotes L.) dan Dosis Pupuk N, P , K pada Pertumbuhan dan Hasil Padi Sawah (Oryza sativa L.) - Husni Thamrin Sebayang; Agus Suryanto; Tristi Indah Dwi Kurnia (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
An experiment to study the effect of water lettuce (Pistia stratiotes L.) application and N, P, K fertilizer on growth and yield of rice was carried out on inceptisol soil at Mojosari Research Farm, Mojokerto, East Java, Indonesia, ± 100 m asl, from December 2007 to April 2008. The experiment was arranged in a Split Plot Design with three replications. Water lettuce application as main plot consisted of four treatments, they are: without water lettuce, water lettuce planted in the rice plot, water lettuce incorporated in the soil, and water lettuce applied as compost. Three dosages of N-P2O5 -K2O fertilizer as sub plot consisted of 135-27-30, 101.25-20.25-22.5, and 67.5-13.5-15 kg ha-1. The results showed that the application of 135-27- 30 or 101.25-20.25-22.5 kg N-P2O5 -K2O ha-1 and the application of water lettuce did not signifi cantly affect rice yields. The combination of 135-27-30 or 135-27-30 kg N-P2O5 -K2O of ha-1 and 3 ton water lettuce compost ha-1 increased the growth of rice at 30 days after sowing. Application of water lettuce did not interact with N, P and K fertilizer application in affecting rice yield components.Keywords: fertilizer, low external input, rice, water lettuce